Essay on scientific denial in times of pandemic (Research, Society and Development, 2021)
Criticism of any concept necessarily involves the ability to understand its origins and scope. Perhaps one of the saddest legacies of post-modernity is denial, when it is understood that it is part of a strategy of domination based on a declared war on Science and Reason. The main scope of this essay is, therefore, to put some basic questions about the origin of scientific denial on the table, even though for them there are no definitive answers. For example, to what extent is it part of a process of valuing fanaticism and individualism? Can the lack of institutionalized scientific dissemination be considered a cause of the current negationism in our country? Is negationism related to the general problem of education? Is there a way to identify its pillars in contemporary society? These are some questions that are discussed in this paper, to which it is urgent to find answers if we are to avoid a huge sociocultural setback.